Performance evaluation of the eICIC technique applied to a heterogeneous 4G mobile network - Eric Michel, DEUSSOM DJOMADJI; FOUBA, Bienvenue Arsene Roger; KENFACK WAMBA, Jean Gutenbert (European Journal of Applied Sciences, 2022)
The evolution of LTE-A (Long Term Evolution -Advanced) has enabled the development of the Heterogeneous Network (HetNet) which uses multiple cell types due to the explosion in the number of connected subscribers. Different cell types of different sizes are deployed to share the load in the heterogeneous network. Unplanned deployment of small cells with low power, planning of the existing network, the power difference between cells; physical and meteorological phenomena affect the signal quality of radio links; crowded areas of metropolises with extremely high traffic hotspots force operators to increase the network capacity in a more economical way by installing small cells Several techniques have been developed in the literature. Among them, eICIC has emerged as the best and is used to overcome these interference problems in the heterogeneous 4G network. The performance evaluation of eICIC has been performed analytically and numerically in the time domain due to its use with the ABS (Almost Blank Subframe) of the OFDM system. The simulation areas are in center of the picocells, in the cell range extension (CRE) areas and in the macrocells. Analytically, we used the signal-to-interference-plus-noise ratio (SINR) to evaluate the bit rate, RSRP and RSRQ. The numerical method consists in proposing an algorithm for calculating the analytical parameters using Matlab software. The results obtained from the simulations are convincing and are not far from those obtained in the literature. The values obtained from the SINR correspond to the SINR-CQI table found in the literature. The throughput calculated in this work in relation to radio conditions (RSRP, RSRQ) reflects everyday realities.